Effect of Extraction Conditions on Purity and Structure of Pectin in Tobacco by CP/MAS 13C NMR Spectroscopy - Zhu, Xiao-Lan; Wang, Yusong; Gao, Yun; Lin, Hui; Chen, Jun (Asian Journal of Chemistry, 2015)
The structure and composition of pectins depend on their source, the method used to extract from other soluble material, the analytical procedures and so on. This study was to investigate the influence of extraction conditions (pH, temperature and extraction time) on the yield, purity and structure of pectin in tobacco by CP/MAS 13C NMR spectroscopy. The results showed that the highest yield of pectin (10.87 %) was obtained at pH 1.5, but the highest purity of pectin (galacturonic acid content, GalA) was obtained at pH 2, which was 78.4 %. The degrees of methylation and acetylation decreased with increasing of acid strength (at pH 1.5-2.5), temperature and extraction time. With stronger acid, higher temperature and longer time, the degrees of methylation and degrees of acetylation of pectin decrease. These data provides a prerequisite for controlling and manipulating pectins processing properties.